INVESTIGATING THE RELATIONSHIP BETWEEN ECONOMIC GROWTH AND HUMAN DEVELOPMENT INDEX: ARE THEY SIMULTANEOUSLY RELATED ? - Nababan, Tongam Sihol; Panjaitan, Raya; Panjaitan, Ferry; Napitupulu, Sungguli (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2024)
This study aims to investigate and prove whether economic growth and the human development index, each of which is influenced by its determinants, have a simultaneous relationship. The data used is secondary data in the form of panel data from North Sumatra Province consisting of 29 districts / cities for the period 2018 - 2022. The analysis method used is simultaneous equation with two stages least square. The study results show that the variables that have a positive and significant effect on economic growth are the output value variable of large and medium industries and the labor force participation rate variable, while the employment opportunity variable has a negative and significant effect on economic growth. The variables that have a positive and significant effect on the human development index variable are the per capita income variable and the life expectancy variable. However, the economic growth variable has a negative and significant effect on the human development index. By using two stages least square analysis, it is found that economic growth does not have a simultaneous relationship with the human development index variable.